Poszerzone łańcuchy wiedzy jako podstawa współpracy między firmą a klientem - Perechuda, Kazimierz (Extended knowledge chains as the basis for the cooperation between company and client., 2006)
The paper presents: the new hypothesis of knowledge management, the statical and dynamical approach in the knowledge creation, the suhproccsses of extended knowledge chain. the role of company in the creation of local knowledge socjety.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 184-189